Determinación del grado y radio de curvatura radicular de incisivos superiores para planificar su tratamiento endodóntico - Bastidas Robayo, Cristopher Alexander (2023)
ABSTRACT: The anatomical variation of the roots and canals of the upper permanent incisors and its impact on the biomechanical preparation in endodontics has been a factor that should be understood and adequately addressed to avoid complications. The main objective of this research work was to determine the degree and radius of root curvature of upper incisors in order to plan endodontic treatment. The main objective was to explain the adequate endodontic treatment according to the degree and radius of average curvature of the upper central and lateral incisor. It was performed by means of a bibliographic study of scientific articles published from 2013 to 2023, using the databases: Pubmed, Elsevier, Scielo, Wiley, Redalyc, a total of 75 scientific articles were collected for the analysis process which were chosen according to criteria of quality of publications by SJR factor and average citation count. It is obtained that endodontic treatment planning can be carried out based on the degree and radius of curvature presented by the upper permanent incisors, making two plans, one for cases of moderate and severe curvature and the other for mild curvature. Concluding that the prevalence of root curvature of the upper incisors worldwide is 46.25% according to the studies analyzed, as well as the root curvature of the upper incisors has a direct implication in endodontic treatment because the omission of this factor can result in complications during treatment.